Perancangan WebView Template Pada Android Studio Arctic Fox Studi Kasus: Dagangrumah.com - Putra, Raden Bagus Dimas; Budi, Eko Setia; Kadafi, Abdul Rahman (JURIKOM (Jurnal Riset Komputer), 2021)
Android is one of the largest mobile operating system platforms today. In the midst of the rapid development of android application technology, many programmers have not learned how to make android applications, evidenced by the number of websites that have adapted to the android application screen but do not yet have android applications. In android application development technology there is a feature called WebView that allows application developers to be able to display content from web pages directly within the application. To make it easier to create applications, the author creates templates by: prototyping Â WebView, formulating problems, studying supporting theories, creating templates, template implementation, as well as documentation of template implementation. In Android Studio Arctic Fox, the application of templates is done with three steps: changing the project name, changing the contents of variables according to the parameters of the relevant website data, and changing the logo. By using WebView templates, the process of creating applications from a website becomes very easy.